Factors Predicting Work Ability among Community Healthcare Providers in Yangon, Myanmar - Wai, Phyu Nyein; Clara, Naw (Makara Journal of Health Research, 2024)
Background: In healthcare organizations, a high level of work ability is necessary for workers to perform their tasks under different working conditions. This study aimed to describe the quality of work life, work environment, and work ability and examine predictors of the work ability of community healthcare providers. Methods: A cross-sectional descriptive study was conducted from May 2020 to July 2020. The study enrolled 284 registered nurses and midwives from 38 public health departments in Yangon, Myanmar. Data were collected using the work-related quality of life scale (WRQoL) 2, work environment impact scale (WEIS-SR), and work ability index (WAI). The multiple regression method was used to analyze predictors of work ability. Results: Overall, 71.13% of the participants were between 26 and 45 years old, and 99.30% were female. High WEIS-SR (61.98 ± 6.38), average WRQoL (106.10 ± 15.63), and good WAI (39.29 ± 4.99) scores were found (p = 0.05). WRQoL was found to be a predictor of the WAI of community healthcare providers (R2 = 0.140, B = 0.124) (p = 0.05). Conclusions: Improving the quality of work life of community healthcare providers will also motivate them to perform their jobs better and thus satisfy their clients.